The Canadian Plastic Surgery Workforce Analysis: Forecasting Future Need - Morzycki, Alexander (Plast Surg (Oakv), 2018)
BACKGROUND: Projecting the demand for plastic surgeons has become increasingly important in a climate of scarce public resource within a single payer health-care system. The goal of this study is to provide a comprehensive workforce update and describe the perceptions of the workforce among Canadian Plastic Surgery residents and surgeons. METHODS: Two questionnaires were developed by a national task force under the Canadian Plastic Surgery Research Collaborative. The surveys were distributed to residents and practicing surgeons, respectively. RESULTS: Two-hundred fifteen (49%) surgeons responded, with a mean age of 51.4 years (standard deviation [SD] = 11.5); 78% were male. Thirty-three percent had been in practice for 25 years or longer. More than half of respondents were practicing in a large urban center. Fifty-nine percent believed their group was going to hire in the next 2 to 3 years; however, only 36% believed their health authority/provincial government had the necessary resources. The mean desired age of retirement was 67 years (SD = 6.4). We predict the surgeons-to-population ratio to be 1.55:100 000 and the graduate-to-retiree ratio to be 2.16:1 within the next 5 to 10 years. Seventy-seven (49%) residents responded. Most were “very satisfied” with their training (61%) and operative experience (90%). Eighty-nine percent of respondents planned to pursue addqitional training after residency, with 70% stating that the current job market was contributing to their decision. Most residents responded that they were concerned with the current job market. CONCLUSIONS: The results of this study predict an adequate number of plastic surgeons will be trained within the next 10 years to suit the population’s requirements; however, there is concern that newly trained surgeons will not have access to the necessary resources to meet growing demands. Furthermore, there is an evident shortage of those practicing in rural areas. Many trainees worry about the availability of jobs, despite evidence of active recruitment. The workforce may benefit from structured career mentorship in residency and improved transparency in hiring practices, particularly to attract young surgeons to smaller communities. It may also benefit from a coordinated national approach to recruitment and succession planning.